Peran Hukum Administrasi Negara sebagai Ilmu Pengetahuan dalam Membangun Transparansi dan Akuntabilitas Sektor Publik - Cahyo Nugroho, Tri; Khan, Aditya Sulthony Ahmad; Jaya, Karman (UNIB Press, 2025)
This study aims to examine the role of administrative law as an academic discipline in strengthening transparency and accountability in the public sector through a systematic literature review. A qualitative approach was employed using a Systematic Literature Review (SLR) design, focusing on the search, selection, and analysis of scholarly publications and international reports related to administrative law, public information disclosure, and governance. The literature reviewed covers works published between 2010 and 2024, obtained from reputable scientific databases. The findings reveal that administrative law plays a dual role: as a normative framework and as a regulatory mechanism to ensure public information disclosure, prevent abuse of authority, and enhance bureaucratic accountability. Three key findings are identified: (1) legal frameworks governing public information disclosure provide legitimacy for transparency practices; (2) administrative law contributes to anti-corruption efforts through the implementation of digital systems such as e-procurement; and (3) the integration of administrative law with bureaucratic reform and global governance standards supports the development of modern, accountable governance. This study concludes that the success of transparency and accountability in the public sector is strongly influenced by the presence of a clear, consistent, and internationally aligned administrative legal framework.